Nutritional and physiological challenges of preparing athletes for the Winter Olympics - Noonan, J.; Close, G. (The Sport and Exercise Scientist, 2014)
Whilst skiing has been an integral part of winter Olympic competition since 1936 (Germany Winter Olympic Games), snowboarding is a progressing sport and was only introduced in the 1998 Japan Winter Olympics. This year, a record number of five snowboard events took place in the Winter Olympics in Sochi, Russia. Despite a growth in professional competition and growing media attention, there is still a lack of understanding of `quality practice` for athlete preparation tailored to meet event-specific needs. This article examines the physiological preparation of snowboard athletes for Sochi 2014 with a specific focus the strength and conditioning and nutritional challenges.